The Hairless Mexican and the Traitor - Maugham W .Somerset (Heinemann Publishers (Oxford) Ltd, 1974)
The Hairless Mexican- It is spring 1915. The war has been on for about nine months. The Mexican is sent to Italy to do a secret job. Ashenden thinks the Mexican is a strange, frightening man. Can he be trusted?... The Traitor- Caypor seems kid and gentle. The things he likes best are simple things like flowers. The things he likes least is war. It is difficult to believe he is a traitor.
Keywords: Juvenile Fiction